المصارف الإسلامية والقدرة على الإستدامة في ظل الأزمات المالية - دراسة مقارنة- (المجلة العراقية للعلوم الاقتصادية, 2018)
The recent financial crisis (mortgage crisis) showed the ability of Islamic banks to absorb shocks, as they were less affected by their repercussions, so that Islamic banks are not to deal with products of financial engineering, which are non-real assets, and that its principles prohibit sale what you don t possess, selling of non-assets and linking funding with assets.The importance of research stems from the importance of Islamic banks, which were able to achieve a distinguished presence on the banking arena, making it a global phenomenon that everyone is moving to take advantage of them. So, the research confirms the hypothesis that possession of Islamic banks a lot of ingredients that have achieved safety and security, which makes them immune to the crisis.To prove the hypothesis of research has been divided into three sections. The first dealing with historical context of the financial and banking crises, with a focus on the mortgage crisis, while the second part, singled out for study of the concept, and status of the strategic objectives of the Islamic banks. The third topic dealt with the causes of the financial crisis to illustrate the possibility of exceeding these reasons by Islamic banks as compared with the conventional banks.